A craniofacial morphology study of patients with obstructive sleep apnes - Hassan, Rozita (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Obstructive sleep apnea (OSA) is a potentially life-threatening condition in which a patient suffers periodic cessations of breathing during sleep. The aim of this study is to develop a data base on the craniofacial morphology of the upper airway morphology and skeletal patterns in PJ!tients with OSA and compare the findings with those of normal subjects. Twenty-five subjects a.s OSA patients and twenty-five as the control group were selected from the Sleep Laboratory by using, Polysomnography. The subjects were adults age ranging 18- . 65 years. Measurements of the body mass index (BMI), neck circumference, lateral cephalometric X-ray, posterior-anterior X2ray, and upper and lower dental study models were taken. CT scan were prescribed for severe OSA cases. The results showed that th~ BMI, length of soft palate, width of soft palate, width of tongue, upper posterior airway space, middle posterior airway space, lower posterior airway space, distance from hyoid bone to mandibular plane, distance from hyoid bone to posterior nasal spine, maxillary width, the neck circumference and cranial base flexure angle significantly increased (P <.001) in OSA patients. The CT scan shown that severe OSA patients have narrowing of pharyox at the level of nasopharynx, oropharynx, and hypopharynx. In conc;lusicm •. trul knowledge of craniofacial morphological differences in OSA patient will facilitate clinical management.